The Origins of Common Identity: Division, Homogenization Policies and Identity Formation in Alsace-Lorraine - Sirus Dehdari; Kai Gehring (Center for Economic Studies and ifo Institute (CESifo), 2018)
We exploit the quasi-exogenous division of the French regions Alsace and Lorraine after the Franco-Prussian War in 1870 due to disagreements in the German leadership to provide evidence of group identity formation within historically homogeneous regions. People in the treated area, which was exposed to repressive homogenization policies aimed to suppress group identity, express a stronger regional identity and support more regional autonomy today. Using a regression discontinuity design at the municipal level, we find that support for two crucial referenda, which would have increased regional autonomy, subscription rates to regional newspapers, and regionalist party votes are significantly higher in the treated area. The results are robust across different specifications and bandwidths, and not driven by language differences, large agglomerations or distance to foreign countries. The differences in regional identity are strongest for the first two age cohorts after World War II and become weaker for later generations.
Keywords: D91; H70; H80; N40; Z19; 330; group identity; regional identity; identity formation; persistence of preferences; homogenization policies; assimilation; Alsace-Lorraine